1998
DOI: 10.1002/(sici)1096-9063(199809)54:1<61::aid-ps780>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Residues and fate of endosulfan on field-grown pepper and tomato

Abstract: : Endosulfan (Thiodan 3 EC), a mixture of a-and b-isomers, was sprayed on 92-day-old Ðeld-grown pepper and tomato at the recommended rate of 0É61 kg AI ha~1. Plant tissue samples were collected at 1 h to 14 days after application and analysed to determine the content and dissipation rate of endosulfan isomers (a-and b-endosulfan) and the major metabolite, endosulfan sulfate. Analysis of samples was accomplished using gas chromatography-mass selective detection (GC-MSD). The results indicated the formation of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(36 citation statements)
references
References 32 publications
2
33
1
Order By: Relevance
“…This can explain the tendency of no or minute levels of residues on cucumber. The range of most detected pesticides levels in cucumber, tomatoes and strawberries coincides with Gil-Gracia [23], Antonious et al [24], Ripley et al [26] and Saldo [27].…”
Section: Gc-ms Detected and Confirmed Pesticide Residues On Cucumbersupporting
confidence: 81%
See 1 more Smart Citation
“…This can explain the tendency of no or minute levels of residues on cucumber. The range of most detected pesticides levels in cucumber, tomatoes and strawberries coincides with Gil-Gracia [23], Antonious et al [24], Ripley et al [26] and Saldo [27].…”
Section: Gc-ms Detected and Confirmed Pesticide Residues On Cucumbersupporting
confidence: 81%
“…According to Gil-Gracia et al [23] levels of methomyl residues were studied on tomatoes and green beans in an experimental greenhouse to establish the effect of the kind of greenhouse, application concentration, species grown and climatic condition on the degradation of the insecticide methomyl. Antonious et al [24] studied the residues and fate of endosulfan on field-grown pepper and tomato. Analysis of samples was accomplished using gas chromatography-mass selective detection (GC-MSD).…”
Section: Introductionmentioning
confidence: 99%
“…Endosulfan, a mixture of a-and b-isomers, is a broad-spectrum insecticide, acaricide and miticide used to control a variety of pests that affect fruit, vegetables and ornamental plants (Berrill et al, 1998). This formulation with two isomers with different water solubilities and volatilities (Antonious et al, 1998) has been studied for its toxicity to aquatic organisms possibly affected by direct applications or drift from aerial spraying (Ernst et al, 1991;Berrill et al, 1998). Accumulated data concerning the toxicity hazard of endosulfan led to the recommendation that it should be replaced by less toxic alternatives wherever possible (Berril et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the high lipophilicity (Antonious et al, 1998), a strong interaction with biomembranes is predictable. It was shown that the endosulfan isomers have significant effects on membrane organization and permeability (Videira et al, 1999(Videira et al, , 2002.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have indicated the potential ecological damage due to the widespread use of synthetic pesticides. [1][2][3][4][5][6] The U.S. Food Quality Protection Act (FQPA) in 1996 initiated a systematic effort to identify and reduce potential risks posed by synthetic pesticides to safeguard public health. Among the provisions of the FQPA is a requirement for the EPA to reassess all synthetic pesticide tolerances (9,700+) within ten years of passage of the act.…”
Section: Introductionmentioning
confidence: 99%